Link Adaptive Relaying with Noncoherent BFSK and DPSK Modulations in Multiple Access Relay Channels - Karabulut, Muhammet Ali; Ozdemir, Ozgur; Ilhan, Haci (IEEE, 2015)
Network coding has recently received significant attention as an innovative approach to improve the throughput of wireless communication systems. The multiple access relay channel (MARC), in which multiple users communicate with a common destination via a relay, is one of the important network coding applications for wireless cooperative communications. In this paper, link adaptive relaying (LAR) approach which combats performance degradation due to error propagation in digital relaying based wireless networks has been applied to the MARC model with noncoherent binary frequency shift keying (BFSK) and differential binary phase shift keying (DPSK) signalings which are among the prominent techniques for eliminating the need for channel estimation by training sequences. Simulation results for Nakagami-m fading channels have shown that the proposed MARC model with LAR scheme outperforms the noncooperative system that involves direct transmissions and overcome the diversity gain reduction due to error propagation.
Keywords: Link adaptive relaying; multiple access relay channel; network coding; noncoherent binary frequency shift keying; differential binary phase shift keying; PERFORMANCE; Computer Science; Engineering; Telecommunications